Qualitative Methods Module 20 - Bailey, Kathleen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The resurgence of gang activities in the 1980s and 1990s has prompted many books and articles about the subject of gangs. According to the literature there are more gangs than in past years, more youth in those gangs, and more communities experiencing gang problems (National Youth Gang Center, 1997). Although students are interested in reading and understanding the qualitative issues surrounding gangs (poverty, identity, peer group involvement, family relationships, power and safety issues, culture, etc,) few students truly understand the depth and breadth of the struggle. Generally, few opportunities arise in their world to challenge their understanding of why youth join gangs. They often have limited ideas of how it feels to be denied equal opportunity, to be in a different place of human standard, justice, mercy, rectitude, and fair play. According to Kegan (1982, pg. 148) "…what they need most of all is a kind of intimate participation in their personal experience of evolution..."